ACCESSIBILITY AND ERGONOMICS IN DISTANCE LEARNING: ACCESSIBILITY AND ERGONOMICS IN DISTANCE LEARNING - Dias, Ana Victoria Pinheiro; Batista, Arthur Bruno Vieira; Tavares Arraes, Bruno; Lima, Carla Braga da Silva; Carolino, Elis Regina da Silva; Lima, Natanael Ramos de; Feitosa, Ankilma do Nascimento Andrade (Brazilian Journal of Production Engineering, 2020)
Introduction: The present study aims to develop a subject using Distance Learning (DL), according to the global teaching trends. This teaching model enables dynamic flexible schedules through a Virtual Learning Environment, in which all content will be available. Objective: To discuss the possibility of implementing the educational methodology in the academic field in distance learning (DL) incorporated into the Accessibility and Ergonomics subject. Background: This research stands out for its relevance to the area of Education, the quality, dynamism and flexibility of teaching-learning promoted by the DL, in addition to the demand for content required by the subject. Methodology: This is the elaboration of an application project on the implementation of the Accessibility and Ergonomics curricular unit by a private higher education institution. The project will last four (04) months. Results: This study will allow obtaining the best mechanism for the implementation of the Accessibility and Ergonomics subject in DL. The implementation of the subject will require: action plan aimed at identifying the material and personal resources necessary for the implementation of the subject; assessment of the feasibility of the action plan; and plan management, which will provide planning for the implementation of new resources, if necessary. With the completion of this study, the distance-learning mode allows students to study at flexible times through an integration of a Virtual Learning Environment, between a DL professor and a student, in which all content will be available.
Keywords: Accessibility; Ergonomics; Distance learning